Assessing the potential protective effects of tirzepatide against renal ischaemia-reperfusion injury in male rats: inhibition of Foxo1 expression and pyroptosis - Abdul-Husseein, Hajir Karim; Adnan Alzubaidi, Fatima (Pharmakeftiki, 2025)
Renal ischaemia-reperfusion injury (RIRI) is a significant contributing factor to acute kidney injury, characterized by inflammation and oxidative stress formation that delay tissue repair. Our study has assessed the nephroprotective effects of tirzepatide on RIRI, through its effect on the forkhead box O1 gene (Foxo1) expression and pyroptosis in male rats. Our study included 24 Wistar rats divided to four groups (n=6 each): a sham group (without an induction of RIRI), a control group (with an induction of RIRI), a vehicle group (receiving an intraperitoneal injection of dimethyl sulfoxide at 1 mg/kg, 1 h before ischaemia), and a tirzepatide-treated group (receiving an intraperitoneal injection of tirzepatide at 1.35 mg/kg, 1 h before ischaemia). Our results revealed that tirzepatide can significantly reduce the kidney injury molecule-1 levels (p=0.027) and the levels of pyroptosis markers caspase-1 (p<0.001) and caspase-11 (p=0.005) in the studied rats’ kidneys. Histopathological analysis of the latter revealed severe injury in the control group, while tirzepatide-treated rats exhibited injury scores under 40%. Additionally, the Foxo1 expression was found to be significantly reduced as a result of the tirzepatide treatment (p=0.031). We concluded that tirzepatide may potentially relieve ischaemic renal damage through the modulation of pyroptosis and inflammatory pathways, thereby highlighting its potential as a targeted therapy for RIRI.